Effect of Hexafluorophosphate and Fluoroethylene Carbonate on Electrochemical Performance and the Surface Layer of Hard Carbon for Sodium‐Ion Batteries. Issue 11 (5th October 2016) - Dahbi, Mouad; Nakano, Takeshi; Yabuuchi, Naoaki; Fujimura, Shun; Chihara, Kuniko; Kubota, Kei; Son, Jin‐Young; Cui, Yi‐Tao; Oji, Hiroshi; Komaba, Shinichi
Abstract: Electrochemical sodium insertion for hard carbon is examined in a cyclic alkylene carbonate based solution containing a NaClO4 or NaPF6 salt with a fluoroethylene carbonate (FEC) additive to study electrolyte dependency for sodium‐ion batteries. NaPF6 ‐based electrolytes provide superior reversibility and cyclability of sodium insertion into hard carbon compared with NaClO4 ‐based ones. The FEC‐derived passivation film improves capacity retention because of better passivation with a thinner surface layer, as revealed by hard and soft X‐ray photoelectron spectroscopy (PES). The use of both the NaPF6 salt and FEC additive results in a synergetic effect on passivation for the hard‐carbon electrode, leading to enhanced cycle performance. Hard‐carbon electrodes with polyvinylidene difluoride binder in propylene carbonate based electrolytes containing NaPF6 and FEC demonstrate excellent capacity retention with a reversible capacity of about 250 mAh g −1 . The difference in capacity retention for the electrolytes is expected to originate as a consequence of the difference in the surface interphase layer formed on the hard‐carbon electrodes. Surface analyses with PES and time‐of‐flight secondary ion mass spectrometry reveal differences in surface and passivation chemistry which depend on the salts, solvents, and FEC additives used for the hard‐carbon negative electrodes. Abstract : Developing a thin skin : The electrochemical properties of hard‐carbon electrodes in sodium cells are examined. NaPF6 ‐based electrolytes provide superior reversibility and cyclability of sodium insertion into hard carbon compared with NaClO4 ‐based ones (see figure). The fluoroethylene carbonate (FEC) additive further improves capacity retention because of better passivation with a thinner surface layer. PVdF=polyvinylidene difluoride.